Nurses Knowledge toward Heparin Intake for Patient’s in Intensive Care Unit at AL- Imam AL-Hussain Medical City in Holy Kerbala - Fatma Makee Mahmood (Journal of Global Pharma Technology, 2017)
Heparin is used to prevent or treat certain blood vessel, heart, and lung conditions. It is used in low doses to prevent the formation of blood clots in certain patients, especially those who must have certain types of surgery or who must remain in bed for a long time. Objective This Study aims to assess nurses’ knowledge toward Heparin Intake for Patient’s in Respiratory care and to find out the association of Respiratory care unit s nurses knowledge with some of socio demographical characteristic (level of education, and years of experience in Respiratory care unit (.Methodology A descriptive study was carried out at respiratory care unit of Baghdad teaching hospitals started from December 25th, 2015 through through end of May, 2016. Non-probability (purposive sample) of (30) nurses, who were working in respiratory care unit, were selected from AL- Imam AL-Hussain Medical City. The data were collected through the use of constructed questionnaire, which consist of two parts (1) Demographic data form that consist 6-items and (2) Nurses’ knowledge form that consist of 27 items, by means of direct interview technique of the nurses. Reliability of the questionnaire was determined through a pilot study and the validity through a panel of (15) experts. Descriptive statistical analysis procedures (frequency, percentage, mean of score) and (person correlation coefficient, contingency coefficient) were used for the data analysis. Were used for the data analysis. Results The findings of the study indicated that there was an adequate knowledge about heparin intake in respiratory care unit. A significant relationship was found between nurses’ knowledge and their level of education and years of experience in respiratory care unit .Recommendations The study recommended that the importance of employing Academic nurse in respiratory care unit, a booklet should be designated and distributed to all nurses who were working in respiratory care unit including the standard actions that should be applied and followed to care for patients in respiratory care unit, and an educational program should be designated to the nurses who were working in respiratory care unit including the standard actions that should be applied to care for patients in respiratory care unit Keywords: Anticoagulant, Heparin, Respiratory care unit Critical Care Nurses.